Meta-Analisis Pengembangan Multimedia Pembelajaran Lectora Inspire Berbasis Multipel Representasi Pada Pembelajaran Kimia - Putra Jaya Telaumbanua; Abdul Hadjranul Fatah; Nopriawan Berkat Asi; I Made Sadiana; Anggi Ristiyana Puspita Sari; Maya Erliza Anggraeni (FKIP Universitas Palangka Raya, 2023)
Media development is an effort to overcome students' difficulties in the learning process. The development of lectora inspire learning media tends to present macroscopic and symbolic aspects. Modification of the syntax of the development model found a lack of suitability of learning objectives for narrative representations in learning materials, and learning content for chemical representations which made media difficult to use. The purpose of this study is to analyze suitability; the syntax of the learning media development model on the theoretical development model syntax, learning objectives on teaching materials, and learning content on chemical representation criteria. This study applies a meta-analysis method with a qualitative approach. The results of the research show that the stage of defining the analysis of student characteristics has not been linked to the stage of constructing a criterion-referenced test (setting test standards). One learning objective was found in thesis A, and 3 learning objectives in thesis C which were categorized as partially appropriate, while the learning objectives in thesis B were all categorized as appropriate to the teaching material. Lectora inspire learning content still has a discrepancy with the chemical representation criteria. Lectora insipre learning media tend to contain the R1 (multiple), R2 (explicit), R3 (fully related and connected), R4 (narration according to representation) and R5 (quite connected ).